Freudian Slip? The Changing Cultural Fortunes of Psychoanalytic Concepts - Haslam, Nick; Ye, Lotus (Frontiers in Psychology, 2019)
It is often argued that psychoanalysis has declined in prominence since its ascendance in the mid-20th century. To assess this claim we examined the trajectory of psychoanalytic concepts from 1900 to 2008 in the massive Google Books database. The changing relative frequency of a sample of English-language psychoanalytic terms was explored and compared to a sample of terms in French. The frequency of the English terms was further explored from 2008 to 2017 using the Corpus of Contemporary American English. The English terms rose steeply from the 1940s and declined steeply from the early 1990s. In contrast, the French terms rose steeply from the 1960s and plateaued from the 1970s. In addition, psychoanalytic terms were markedly more prominent in French since the 1960s. The findings are discussed in the context of historical trends in the reception of psychoanalysis in the Anglophone and Francophone worlds.